Kualitas Mikrobiologis Daging Dada Ayam Broiler Direndam dalam Cairan Fermentasi Kubis (Brassica Oleracea) Sebagai Biopreservatif Selama Penyimpanan Suhu Dingin (±4ºc) - Afriani, Afriani; Putri, Rela; Filawati, Filawati (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to determine the effect of cold storage time on broiler chicken breast meat soaked in cabbage fermentation liquid on microbiological quality. The experimental design used was a Completely Randomized Design (CRD) with 5 treatments and 4 replications. If the treatment used has a significant effect on the variable, then it is continued with the Duncan Multiple Range Test. The treatment used was cold storage of broiler chicken breast meat that had been soaked in cabbage fermentation liquid, namely without cold storage (P0), storage for 2 days (P1), storage for 4 days (P2), storage for 6 days (P3) and storage for 8 days (P4). The results of the analysis of variance showed that cold storage had no significant effect (P> 0.05) on total microbes, total lactic acid bacteria, and total Escherichia coli. It was concluded that cold storage (±4°C) of broiler chicken breast meat soaked in fermented cabbage (Brassica oleracea) liquid for up to 8 days was able to maintain total microbes and lactic acid bacteria (LAB). The total microbes are still below the Indonesian National Standard (SNI) and the total Escherichia coli has exceeded the Indonesian National Standard (SNI) limit.